VERSTEK DECISION POWER ON UNDER-HANDS SELLING WHICH THE SELLER DOESN'T EXIST - Ratna Khairani; Rahmida Erliyani; Anang S hophan Tornado (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2023)
The transfer of land rights is the transfer of land rights from the old right holder to the new right holder according to the provisions of the applicable laws and regulations. Land law in Indonesia requires the transfer of land rights to be carried out before the Land Deed Official (PPAT), because basically buying and selling land must meet clear and cash requirements. Government Regulation Number 24 of 1997 Concerning Land Registration in Article 37 paragraph (1) states that "Transfers of land rights and ownership rights to apartment units through buying and selling, exchange, grants, entry into the company and other legal actions for transferring rights, except for transfers of rights through auctions, can only be registered if proven by a deed drawn up by the PPAT who is authorized according to the provisions of the applicable laws and regulations." This is what happened in the decision of the Batulicin District CourtNumber: 68/Pdt.G/2021/PN Btn, where the sale and purchase is carried out underhanded and when registration is desired, the whereabouts of the seller cannot be identified, so the sale and purchase cannot be transferred and registered, because one of the requirements for land registration is there is a deedauthentic which proves that it is true that a legal act of sale and purchase has taken place, so that the making of the sale and purchase deed is hampered. The problem that the author raises in this study is how is the verstek decision that has been inkracht regarding the Registration of Transfer of Land Rights and what is the validity of the making of the Deed of Sale and Purchase (AJB) by PPAT based on the verstek decision? The results in this study are that decisions that have permanent legal force can be enforced, where decisions have binding legal force (binding force), strength of proof (Proving Power) and powerExecutorial (Executorial Force). So the deed can be said to be valid because until now, no party feels that they have been harmed, or that there has been a lawsuit filed against the PPAT concerned regarding the confusion over the existence of the deed